Association between HPV with penile carcinoma: a review - Carvalho, Newton Sergio de; Kannenberg, Ana Paula; Munaretto, Cristine; Yoshioka, Danila; Absy, Maria Cecilia V; Ferreira, Miriam A; Tambara Filho, Renato (Brazilian Journal of Sexually Transmitted Diseases, 2007)
This article consists of a review of the theme the association of Human Papillomavirus, or HPV, and penile cancer. This association has been confir-med through research based on electronic periodicals and internal medicine and surgery books, mainly referring to warty and squamous cell carcino-ma types of penile cancer. The main types of HPV related to the discovery of the disease were the 16 and 18. Chan et al.1has found a HPV 16 orHPV 18 DNA prevalence in penile cancer of 15%, whereas the detection rate in a study by Tornesello et al.2was 46,3%. Despite the conclusions, thesmall amount of data and the novelty of the theme require further studies. The relation of the presence of HPV to the patients’ survival is still a topicthat is open to investigation.